The Effectiveness of Reciprocal Learning Methods on Volleyball Passing Skills in Class V Elementary School Students - Firmansah, Deri; Afriana, Santy; Cicilia, Winda (Universitas Islam Negeri Raden Intan Lampung, 2023)
The aim of the research was to determine the effectiveness of the reciprocal learning method on volleyball passing skills in class V students of Madrasah Ibtidaiyah Negeri. The research method uses a quasi- experiment with a posttest only control design . Data collection techniques using volleyball passing skills tests and documentation. Data analysis uses validity and reliability. Prerequisite analysis uses the normality test, homogeneity test, and t test. The results of research from hypothesis testing show that the posttest results of students in the experimental class obtained a score of 72 while those in the control class obtained a score of 62. The lowest score for the experimental class was 52 and the control class obtained a score of 47. The mean central tendency measure for the experimental class was 60.43 and for the control class amounting to 53.70. The size of group variation which includes the range for the experimental class is 20 and the control class is 15. Using the reciprocal learning method is more effective than the scientific learning model . It can be concluded that there is a difference in the effectiveness of volleyball passing skills using the reciprocal learning method and the average volleyball passing skills of students in the experimental group and the control group.